Предмет: Алгебра,
автор: peredneva1999
Решите уравнения:
5х+3(-1-х)=-8х-8
3х-6(1+х)=-9х+9
-3х+5(-9+4х)=-х-4
-6х-4(9-7х)=-5х+1
Ответы
Автор ответа:
2
а) 5х-3-3х=-8х-8
10х=-5
х=-0.5
б) 3х-6-6х=9-9х
6х=3
х=0.5
в) -3х-45+20х=-х-4
18х=41
х=2
г) -х-36+28х=1
27х=37
х = 1,(370) =
10х=-5
х=-0.5
б) 3х-6-6х=9-9х
6х=3
х=0.5
в) -3х-45+20х=-х-4
18х=41
х=2
г) -х-36+28х=1
27х=37
х = 1,(370) =
Похожие вопросы
Предмет: Математика,
автор: Челоовек228
Предмет: Математика,
автор: alexaorel09
Предмет: Математика,
автор: marikawaii27i
Предмет: Физика,
автор: mamaluga0
Предмет: Химия,
автор: MrLeonDono